Covid-19 pandemic and the motivations for demanding health service in indigenous villages - Aridiane Alves Ribeiro; Lídia Aparecida Rossi
ABSTRACT Objective: To discuss the fundamental aspects in the establishment of preventive measures to tackle covid-19 among indigenous people in view of the motivations for seeking health care in villages of the Terra Indígena Buriti, Mato Grosso do Sul, Brazil. Methods: Theoretical-reflective study based on assumptions of the National Health System and previous ethnographic research that enabled the identification of the motivations to seek health care in Buriti villages. Results: Indigenous people seek health centers for health care programs assistance, treatment of cases they cannot resolve and to chat. Such motivations were the basis for discussing the indigenization process in the confrontation of the new coronavirus pandemic in indigenous lands. Final considerations: The motivations for seeking health care show the physical and social vulnerability of the Terena ethnicity. The effectiveness of the social isolation measure in the villages depends on the dialogue with indigenous leaders, professional engagement and intersectoral actions.